2016
DOI: 10.1542/peds.2015-0039
|View full text |Cite
|
Sign up to set email alerts
|

Local Pharmacy Partnership to Prevent Pediatric Asthma Reutilization in a Satellite Hospital

Abstract: The World Health Organization 2003 report on medication adherence 1 quoted Haynes that "increasing the effectiveness of adherence interventions may have a far greater impact on the health of the population than any improvement in specific medical treatments." An obvious, yet critical, component to medication adherence is access to medications; consequently the failure either to fill new prescriptions or to refill existing ones is a critical point of failure in the postdischarge care of patients. 1, 2 Previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…There is limited evidence for effectiveness of specific interventions to improve pediatric discharge efficiency. Many interventions have been studied in limited contexts, such as implementation of a discharge risk assessment, 10 a "medications-in-hand" policy on hospital discharge, 11 or a ward discharge coordinator to schedule outpatient follow-up. In several studies, researchers have shown that quality improvement (QI) methods can leverage existing resources and account for local needs to improve discharge efficiency without compromising care quality or family satisfaction.…”
mentioning
confidence: 99%
“…There is limited evidence for effectiveness of specific interventions to improve pediatric discharge efficiency. Many interventions have been studied in limited contexts, such as implementation of a discharge risk assessment, 10 a "medications-in-hand" policy on hospital discharge, 11 or a ward discharge coordinator to schedule outpatient follow-up. In several studies, researchers have shown that quality improvement (QI) methods can leverage existing resources and account for local needs to improve discharge efficiency without compromising care quality or family satisfaction.…”
mentioning
confidence: 99%
“…4,17 Although a relationship between medications and risk of return visits has been previously described, we did not evaluate medication use at discharge. 18 Lastly, we did not have information regarding adherence to evidence-based practices during transition from the ED to inpatient units, all of which have been identified as factors that may influence readmissions. [19][20][21][22][23][24]…”
Section: Discussionmentioning
confidence: 99%
“…4 In addition, patients discharged with their asthma medications in-hand have been shown to have a decreased risk of emergency department visits in single centers. 6,7 In these studies, researchers have highlighted important system changes to increase medication possession at the time of discharge, for example, focusing on establishing a discharge medication delivery service 6 or establishing partnerships with community pharmacies. 7 However, to the best of our knowledge, our project is the first to report on a specific strategy, the multidisciplinary huddle, to overcome identified barriers in facilitating medications in-hand at discharge and establish clear closed-loop communication for discharge planning.…”
Section: Figurementioning
confidence: 99%
“…5 Recently, a few hospital systems have focused on increasing medication access by ensuring that patients are discharged from their inpatient encounter with their asthma medications in their possession. [6][7][8][9] In these single-center efforts, increasing medications inhand at discharge has been shown to increase patient satisfaction and decrease health care reuse. 6,7,10 Our institution, the Children's National Medical Center, admits ∼1400 children with asthma annually, which is ∼10% of annual admissions to the hospital.…”
mentioning
confidence: 99%
See 1 more Smart Citation